MISE A NIVEAU, GOUVERNANCE ET PERFROMANCE DE LA PME PRIVEE ALGERIENNE :« LE CAS DE LA PME GCP « JUTOP » : 2004 - 2014 » - Hichem Sofiane SALAOUATCHI; SANDRA SAIBI; BOUALEM ALIOUAT (Revue des Sciences Humaines)
In a socio-economic environment characterized by very frequent mutations, the small and medium private Algerian enterprise (SME), going through a difficult experience to go to the market economy. This company will revise its management style, something already made in its competitors who practice methods of effective management and governance. Given this situation, the stakeholders in this sector are forced to upgrade their business.